Making waves: toward systems-level interpretation of hormonal and endogenous biomarkers in wastewater-based epidemiology - Ahmed S. Abouhend; Walid A. Hanafy; Christopher Watt; Raphael C. Nnachi; Prashant Shenoy; Caitlyn S. Butler (Water Research, 2026)

Pediatric oral cavity physiologically based pharmacokinetic model to predict pharmacokinetics of mucoadhesive atropine gel to treat sialorrhea - Madison Parrot; Nancy Murphy; Joseph E. Rower; Christopher A. Reilly; Danielle Green; Ariel Tarrell; Kevin Watt; Venkata Yellepeddi (Journal of Pharmacokinetics and Pharmacodynamics, 2026)

Metagenomic Insights Into Red Sea Biodiversity Across the Web of Life - Elisa Laiolo; Christopher A. Hempel; Balegh A. Abukabbos; Omar I. Abunayyan; Intikhab Alam; Taiba Alamoudi; Wejdan A. Alkhaldi; Zuhair M. Almubarak; Hamad A. Alnashri; Afrah Alothman; Tareq H. Alqahtani; Khalid A. Alshaikh; et al. (Environmental Microbiology, 2026)
Earth's biodiversity is central to ecosystem health and resilience, providing essential functions and services. The Red Sea is a recognised marine biodiversity hotspot with high endemism and unique environmental conditions that support extensive but poorly resolved biodiversity. Here, we applied metagenomic analyses to sediment samples collected from coastal to deep‐sea environments during the Red Sea Decade Expedition 2022 to characterise biodiversity across the web of life. From a single shotgun assay per sample, this approach simultaneously characterised the sediment microbiome, which amplicon‐based surveys recover only through parallel, targeted assays, and extended detection to higher eukaryotes. Using high‐throughput sequencing, we generated 12.8 billion sequences, revealing taxa covering all domains of life. Although eukaryotic sequences represented only 0.7% of the taxonomically annotated dataset, we managed to identify 679 eukaryotic families. Prokaryotic diversity was high, as expected in a basin‐scale sampling coupled with high sequencing depth, with groups covering a wide functional array. Community structure analyses revealed depth‐driven stratification of open‐ocean benthic microbial communities and latitudinal structuring of coastal benthic eukaryotes. Overall, this dataset provides an empirical reliability–coverage trade‐off with direct consequences for the design of eDNA monitoring programmes targeting conservation‐priority taxa, and clear priorities for taxa specific reference‐database expansion.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Challenges and opportunities integrating remote sensing for mangrove conservation in Papua New Guinea's complex natural and human landscapes - Midhun Mohan; Ewane Basil Ewane; Lara G. Moussa; Michael S. Watt; Peter I. Macreadie; Christopher J. Owers; Daria Agnieszka Karpowicz; Ian Reuben; Willie Doaemo (Regional Studies in Marine Science, 2025)

Fault timing and depocentre development in the northern Perth Basin during the evolution of the East Gondwana rift - Christopher Watts; Chris Elders; Mitchell O’Mara; Nicholas E. Timms; Hugo K.H. Olierook (Gondwana Research, 2025)

Increased rhinovirus replication following corticosteroid and air pollution exposures - Ryan D. Huff; Nataly El-Bittar; Emily R. Watts; Michael Yoon; Tina Afshar; Shahina Wiehler; Neeloffer Mookherjee; Christopher F. Rider; David Proud; Chris Carlsten (Environmental Research, 2025)

Participant Preferences to Inform the Development of Theory-Driven, Digitally Delivered Cooking Interventions Using the Behavior Change Wheel - Susan Veldheer; Christina Scartozzi; Benjamin Watt; Olivia W. Thomas; Shari Hrabovsky; Christopher N. Sciamanna (Journal of Nutrition Education and Behavior, 2025)

Decreases in chimpanzee respiratory disease signs and enteric viral quantity following implementation of anthroponotic disease prevention protocols at a long-term research site - Jacob D. Negrey; Samuel Angedakin; Rachna B. Reddy; Aaron A. Sandel; Salmah Jombela; Erone Akamumpa; Christopher Aliganyira; Charles Birungi; Davis Kalunga; Brian Kamugyisha; Diana Kanweri; Godfrey Mbabazi; et al. (Biological Conservation, 2025)

Sediment and soil source apportionment using geochemical fingerprinting techniques in the Winam Gulf, Lake Victoria - Olivier S. Humphrey; Job Isaboke; Odipo Osano; Christopher Mulanda Aura; William H. Blake; Michael J. Watts (CATENA, 2025)

Uptake of technetium and iodine (I−, IO3− and organo-I) by pecan biochar - Peng Lin; Brennan Ferguson; Karah M. Greene; Wei Xing; Chen Xu; Christopher E. Bagwell; Donald W. Watts; Daniel I. Kaplan (Journal of Environmental Radioactivity, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Local administration of irinotecan using an implantable drug delivery device stops high-grade glioma tumor recurrence in a glioblastoma tumor model - Dina Abdelnabi; Sarah Lastakchi; Colin Watts; Hannah Atkins; Shawn Hingtgen; Alain Valdivia; Christopher McConville (Drug Delivery and Translational Research, 2024)
The treatment for Glioblastoma is limited due to the presence of the blood brain barrier, which restricts the entry of chemotherapeutic drugs into the brain. Local delivery into the tumor resection margin has the potential to improve efficacy of chemotherapy. We developed a safe and clinically translatable irinotecan implant for local delivery to increase its efficacy while minimizing systemic side effects. Irinotecan-loaded implants were manufactured using hot melt extrusion, gamma sterilized at 25 kGy, and characterized for their irinotecan content, release, and drug diffusion. Their therapeutic efficacy was evaluated in a patient-derived xenograft mouse resection model of glioblastoma. Their safety and translatability were evaluated using histological analysis of brain tissue and serum chemistry analysis. Implants containing 30% and 40% w/w irinotecan were manufactured without plasticizer. The 30% and 40% implants showed moderate local toxicity up to 2- and 6-day post-implantation. Histopathology of the implantation site showed signs of necrosis at days 45 and 14 for the 30% and 40% implants. Hematological analysis and clinical chemistry showed no signs of serious systemic toxicity for either implant. The 30% implants had an 80% survival at day 148, with no sign of tumor recurrence. Gamma sterilization and 12-month storage had no impact on the integrity of the 30% implants. This study demonstrates that the 30% implants are a promising novel treatment for glioblastoma that could be quickly translated into the clinic. Graphical Abstract

Effects of interactions between anthropogenic stressors and recurring perturbations on ecosystem resilience and collapse - David A. Keith; Doug H. Benson; Ian R. C. Baird; Laura Watts; Christopher C. Simpson; Martin Krogh; Sarsha Gorissen; Jose R. Ferrer‐Paris; Tanya J. Mason (Conservation Biology, 2023)
Insights into declines in ecosystem resilience and their causes and effects can inform preemptive action to avoid ecosystem collapse and loss of biodiversity, ecosystem services, and human well‐being. Empirical studies of ecosystem collapse are rare and hampered by ecosystem complexity, nonlinear and lagged responses, and interactions across scales. We investigated how an anthropogenic stressor could diminish ecosystem resilience to a recurring perturbation by altering a critical ecosystem driver. We studied groundwater‐dependent, peat‐accumulating, fire‐prone wetlands known as upland swamps in southeastern Australia. We hypothesized that underground mining (stressor) reduces resilience of these wetlands to landscape fires (perturbation) by diminishing groundwater, a key ecosystem driver. We monitored soil moisture as an indicator of ecosystem resilience during and after underground mining. After landscape fire, we compared responses of multiple state variables representing ecosystem structure, composition, and function in swamps within the mining footprint with unmined reference swamps. Soil moisture declined without recovery in swamps with mine subsidence (i.e., undermined), but was maintained in reference swamps over 8 years (effect size 1.8). Relative to burned reference swamps, burned undermined swamps showed greater loss of peat via substrate combustion; reduced cover, height, and biomass of regenerating vegetation; reduced postfire plant species richness and abundance; altered plant species composition; increased mortality rates of woody plants; reduced postfire seedling recruitment; and extirpation of a hydrophilic animal. Undermined swamps therefore showed strong symptoms of postfire ecosystem collapse, whereas reference swamps regenerated vigorously. We found that an anthropogenic stressor diminished the resilience of an ecosystem to recurring perturbations, predisposing it to collapse. Avoidance of ecosystem collapse hinges on early diagnosis of mechanisms and preventative risk reduction. It may be possible to delay or ameliorate symptoms of collapse or to restore resilience, but the latter appears unlikely in our study system due to fundamental alteration of a critical ecosystem driver. Efectos de las interacciones entre los estresantes antropogénicos y las perturbaciones recurrentes sobre la resiliencia y el colapso de los ecosistemas

Ecosystem-atmosphere CO2 exchange from semiarid mangroves in the Gulf of California - Martha L. Vargas-Terminel; Julio C. Rodríguez; Enrico A. Yépez; Carlos A. Robles-Zazueta; Christopher Watts; Jaime Garatuza-Payán; Rodrigo Vargas; Zulia M. Sanchez-Mejia (Journal of Arid Environments, 2023)

The Watts Connectedness Scale: a new scale for measuring a sense of connectedness to self, others, and world - Rosalind Watts; Hannes Kettner; Dana Geerts; Sam Gandy; Laura Kartner; Lea Mertens; Christopher Timmermann; Matthew M. Nour; Mendel Kaelen; David Nutt; Robin Carhart-Harris; Leor Roseman (Psychopharmacology, 2022)
Rationale A general feeling of disconnection has been associated with mental and emotional suffering. Improvements to a sense of connectedness to self, others and the wider world have been reported by participants in clinical trials of psychedelic therapy. Such accounts have led us to a definition of the psychological construct of ‘connectedness’ as ‘a state of feeling connected to self, others and the wider world’. Existing tools for measuring connectedness have focused on particular aspects of connectedness, such as ‘social connectedness’ or ‘nature connectedness’, which we hypothesise to be different expressions of a common factor of connectedness. Here, we sought to develop a new scale to measure connectedness as a construct with these multiple domains. We hypothesised that (1) our scale would measure three separable subscale factors pertaining to a felt connection to ‘self’, ‘others’ and ‘world’ and (2) improvements in total and subscale WCS scores would correlate with improved mental health outcomes post psychedelic use. Objectives To validate and test the ‘Watts Connectedness Scale’ (WCS). Methods Psychometric validation of the WCS was carried out using data from three independent studies. Firstly, we pooled data from two prospective observational online survey studies. The WCS was completed before and after a planned psychedelic experience. The total sample of completers from the online surveys was N = 1226. Exploratory and confirmatory factor analysis were performed, and construct and criterion validity were tested. A third dataset was derived from a double-blind randomised controlled trial (RCT) comparing psilocybin-assisted therapy ( n = 27) with 6 weeks of daily escitalopram ( n = 25) for major depressive disorder (MDD), where the WCS was completed at baseline and at a 6-week primary endpoint. Results As hypothesised, factor analysis of all WCS items revealed three main factors with good internal consistency. WCS showed good construct validity. Significant post-psychedelic increases were observed for total connectedness scores (η2 = 0.339, p < 0.0001), as well as on each of its subscales ( p < 0.0001). Acute measures of ‘mystical experience’, ‘emotional breakthrough’, and ‘communitas’ correlated positively with post-psychedelic changes in connectedness ( r = 0.42, r = 0.38, r = 0.42, respectively, p < 0.0001). In the RCT, psilocybin therapy was associated with greater increases in WCS scores compared with the escitalopram arm ( η p 2 = 0.133, p = 0.009). Conclusions The WCS is a new 3-dimensional index of felt connectedness that may sensitively measure therapeutically relevant psychological changes post-psychedelic use. We believe that the operational definition of connectedness captured by the WCS may have broad relevance in mental health research.

Environmental DNA Methods for Ecological Monitoring and Biodiversity Assessment in Estuaries - Raman P. Nagarajan; Mallory Bedwell; Ann E. Holmes; Thiago Sanches; Shawn Acuña; Melinda Baerwald; Matthew A. Barnes; Scott Blankenship; Richard E. Connon; Kristy Deiner; Daphne Gille; Caren S. Goldberg; et al. (Estuaries and Coasts, 2022)
Environmental DNA (eDNA) detection methods can complement traditional biomonitoring to yield new ecological insights in aquatic systems. However, the conceptual and methodological frameworks for aquatic eDNA detection and interpretation were developed primarily in freshwater environments and have not been well established for estuaries and marine environments that are by nature dynamic, turbid, and hydrologically complex. Environmental context and species life history are critical for successful application of eDNA methods, and the challenges associated with eDNA detection in estuaries were the subject of a symposium held at the University of California Davis on January 29, 2020 ( https://marinescience.ucdavis.edu/engagement/past-events/edna ). Here, we elaborate upon topics addressed in the symposium to evaluate eDNA methods in the context of monitoring and biodiversity studies in estuaries. We first provide a concise overview of eDNA science and methods, and then examine the San Francisco Estuary (SFE) as a case study to illustrate how eDNA detection can complement traditional monitoring programs and provide regional guidance on future potential eDNA applications. Additionally, we offer recommendations for enhancing communication between eDNA scientists and natural resource managers, which is essential for integrating eDNA methods into existing monitoring programs. Our intent is to create a resource that is accessible to those outside the field of eDNA, especially managers, without oversimplifying the challenges or advantages of these methods.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Landscape Controls on Nutrient Stoichiometry Regulate Lake Primary Production at the Margin of the Greenland Ice Sheet - Clay Prater; Joanna E. Bullard; Christopher L. Osburn; Sarah L. Martin; Michael J. Watts; N. John Anderson (Ecosystems, 2022)
Global change is reshaping the physical environment and altering nutrient dynamics across the Arctic. These changes can affect the structure and function of biological communities and influence important climate-related feedbacks (for example, carbon (C) sequestration) in biogeochemical processing hot spots such as lakes. To understand how these ecosystems will respond in the future, this study examined recent (< 10 y) and long-term (1000 y) shifts in autotrophic production across paraglacial environmental gradients in SW Greenland. Contemporary lake temperatures and light levels increased with distance from the ice sheet, along with dissolved organic C (DOC) concentrations and total nitrogen:total phosphorus (TN:TP) ratios. Diatom production measured as biogenic silica accumulation rates (BSiARs) and diatom contribution to microbial communities declined across these gradients, while total production estimated using C accumulation rates and δ 13 C increased, indicating that autochthonous production and C burial are controlled by microbial competition and competitive displacement across physiochemical gradients in the region. Diatom production was generally low across lakes prior to the 1800’s AD but has risen 1.5–3× above background levels starting between 1750 and 1880 AD. These increases predate contemporary regional warming by 115–250 years, and temperature stimulation of primary production was inconsistent with paleorecords for ~ 90% of the last millennium. Instead, primary production appeared to be more strongly related to N and P availability, which differs considerably across the region due to lake landscape position, glacial activity and degree of atmospheric nutrient deposition. These results suggest that biological responses to enhanced nutrient supply could serve as important negative feedbacks to global change.

Toward a Global Public Repository of Community Protocols to Encourage Best Practices in Biomolecular Ocean Observing and Research - Robyn M. Samuel; Raissa Meyer; Pier Luigi Buttigieg; Neil Davies; Nicholas W. Jeffery; Christopher Meyer; Christina Pavloudi; Kathleen Johnson Pitz; Maxime Sweetlove; Susanna Theroux; Jodie van de Kamp; Alison Watts (Frontiers in Marine Science, 2021)
Biomolecular ocean observing and research is a rapidly evolving field that uses omics approaches to describe biodiversity at its foundational level, giving insight into the structure and function of marine ecosystems over time and space. It is an especially effective approach for investigating the marine microbiome. To mature marine microbiome research and operations within a global ocean biomolecular observing network (OBON) for the UN Decade of Ocean Science for Sustainable Development and beyond, research groups will need a system to effectively share, discover, and compare “omic” practices and protocols. While numerous informatic tools and standards exist, there is currently no global, publicly-supported platform specifically designed for sharing marine omics [or any omics] protocols across the entire value-chain from initiating a study to the publication and use of its results. Toward that goal, we propose the development of the Minimum Information for an Omic Protocol (MIOP), a community-developed guide of curated, standardized metadata tags and categories that will orient protocols in the value-chain for the facilitated, structured, and user-driven discovery of suitable protocol suites on the Ocean Best Practices System. Users can annotate their protocols with these tags, or use them as search criteria to find appropriate protocols. Implementing such a curated repository is an essential step toward establishing best practices. Sharing protocols and encouraging comparisons through this repository will be the first steps toward designing a decision tree to guide users to community endorsed best practices.

Rice Grain Cadmium Concentrations in the Global Supply-Chain - Zhengyu Shi; Manus Carey; Caroline Meharg; Paul N. Williams; Antonio J. Signes-Pastor; Eridha Ayu Triwardhani; Febbyandi Isnanda Pandiangan; Katrina Campbell; Christopher Elliott; Ernest M. Marwa; Xiao Jiujin; Júlia Gomes Farias; et al. (Exposure and Health, 2020)
One of cadmium’s major exposure routes to humans is through rice consumption. The concentrations of cadmium in the global polished (white), market rice supply-chain were assessed in 2270 samples, purchased from retailers across 32 countries, encompassing 6 continents. It was found on a global basis that East Africa had the lowest cadmium with a median for both Malawi and Tanzania at 4.9 μg/kg, an order of magnitude lower than the highest country, China with a median at 69.3 μg/kg. The Americas were typically low in cadmium, but the Indian sub-continent was universally elevated. In particular certain regions of Bangladesh had high cadmium, that when combined with the high daily consumption rate of rice of that country, leads to high cadmium exposures. Concentrations of cadmium were compared to the European Standard for polished rice of 200 μg/kg and 5% of the global supply-chain exceeded this threshold. For the stricter standard of 40 μg/kg for processed infant foods, for which rice can comprise up to 100% by composition (such as rice porridges, puffed rice cereal and cakes), 25% of rice would not be suitable for making pure rice baby foods. Given that rice is also elevated in inorganic arsenic, the only region of the world where both inorganic arsenic and cadmium were low in grain was East Africa.

Correction to: Global Sourcing of Low-Inorganic Arsenic Rice Grain - Manus Carey; Caroline Meharg; Paul Williams; Ernest Marwa; Xiao Jiujin; Júlia Gomes Farias; P. Mangala C. S. De Silva; Antonio Signes-Pastor; Ying Lu; Fernando Teixeira Nicoloso; Laurie Savage; Katrina Campbell; et al. (Exposure and Health, 2020)

Global Sourcing of Low-Inorganic Arsenic Rice Grain - Manus Carey; Caroline Meharg; Paul Williams; Ernest Marwa; Xiao Jiujin; Júlia Gomes Farias; P. Mangala C. S. De Silva; Antonio Signes-Pastor; Ying Lu; Fernando Teixeira Nicoloso; Laurie Savage; Katrina Campbell; et al. (Exposure and Health, 2020)
Arsenic in rice grain is dominated by two species: the carcinogen inorganic arsenic (the sum of arsenate and arsenite) and dimethylarsinic acid (DMA). Rice is the dominant source of inorganic arsenic into the human diet. As such, there is a need to identify sources of low-inorganic arsenic rice globally. Here we surveyed polished (white) rice across representative regions of rice production globally for arsenic speciation. In total 1180 samples were analysed from 29 distinct sampling zones, across 6 continents. For inorganic arsenic the global $$\tilde{x}$$ x ~ was 66 μg/kg, and for DMA this figure was 21 μg/kg. DMA was more variable, ranging from < 2 to 690 μg/kg, while inorganic arsenic ranged from < 2 to 399 μg/kg. It was found that inorganic arsenic dominated when grain sum of species was < 100 μg/kg, with DMA dominating at higher concentrations. There was considerable regional variance in grain arsenic speciation, particularly in DMA where temperate production regions had higher concentrations. Inorganic arsenic concentrations were relatively consistent across temperate, subtropical and northern hemisphere tropical regions. It was only in southern hemisphere tropical regions, in the eastern hemisphere that low-grain inorganic arsenic is found, namely East Africa ( $$\tilde{x}$$ x ~ < 10 μg/kg) and the Southern Indonesian islands ( $$\tilde{x}$$ x ~ < 20 μg/kg). Southern hemisphere South American rice was universally high in inorganic arsenic, the reason for which needs further exploration.

Morphological predictors of swimming speed performance in river and reservoir populations of Australian smelt Retropinna semoni - Daniel Phillip Svozil; Lee J. Baumgartner; Christopher J. Fulton; Richard Keller Kopf; Robyn J. Watts (Journal of Fish Biology, 2020)
Dam construction is a major driver of ecological change in freshwater ecosystems. Fish populations have been shown to diverge in response to different flow velocity habitats, yet adaptations of fish populations to river and reservoir habitats created by dams remains poorly understood. We aimed to evaluate divergence of morphological traits and prolonged swimming speed performance between lotic and lentic populations of Australian smelt Retropinna semoni and quantify the relationship between prolonged swimming speed performance and morphology. Prolonged swimming speed performance was assessed for 15 individuals from each of three river and two reservoir populations of R. semoni using the critical swimming speed test (U crit ). Body shape was characterized using geometric morphometrics, which was combined with fin aspect ratios and standard length to assess morphological divergence among the five populations. Best subsets model‐selection was used to identify the morphological traits that best explain U crit variation among individuals. Our results indicate R. semoni from river populations had significantly higher prolonged swimming speed performance (U crit = 46.61 ± 0.98 cm s −1 ) than reservoir conspecifics (U crit = 35.57 ± 0.83 cm s −1 ; F 1,74 = 58.624, Z = 35.938, P R. semoni sampled from river populations had significantly higher fin aspect ratios (AR caudal = 1.71 ± 0.04 and 1.29 ± 0.02 respectively; F (1,74) = 56.247, Z = 40.107, P pectoral = 1.85 ± 0.03 and 1.33 ± 0.02 respectively; F (1,74) = 7.156, Z = 4.055, P crit was most strongly correlated with pectoral and caudal fin aspect ratios (R 2 adj = 0.973, AIC c = 41.54). Body shape, however, was subject to a three‐way interaction among population, habitat and sex effects (F 3,74 = 1.038. Z = 1.982; P

Large birds travel farther in homogeneous environments - Marlee A. Tucker; Olga Alexandrou; Richard O. Bierregaard; Keith L. Bildstein; Katrin Böhning‐Gaese; Chloe Bracis; John N. Brzorad; Evan R. Buechley; David Cabot; Justin M. Calabrese; Carlos Carrapato; Andre Chiaradia; et al. (Global Ecology and Biogeography, 2019)
Aim Animal movement is an important determinant of individual survival, population dynamics and ecosystem structure and function. Nonetheless, it is still unclear how local movements are related to resource availability and the spatial arrangement of resources. Using resident bird species and migratory bird species outside the migratory period, we examined how the distribution of resources affects the movement patterns of both large terrestrial birds (e.g., raptors, bustards and hornbills) and waterbirds (e.g., cranes, storks, ducks, geese and flamingos). Location Global. Time period 2003–2015. Major taxa studied Birds. Methods We compiled GPS tracking data for 386 individuals across 36 bird species. We calculated the straight‐line distance between GPS locations of each individual at the 1‐hr and 10‐day time‐scales. For each individual and time‐scale, we calculated the median and 0.95 quantile of displacement. We used linear mixed‐effects models to examine the effect of the spatial arrangement of resources, measured as enhanced vegetation index homogeneity, on avian movements, while accounting for mean resource availability, body mass, diet, flight type, migratory status and taxonomy and spatial autocorrelation. Results We found a significant effect of resource spatial arrangement at the 1‐hr and 10‐day time‐scales. On average, individual movements were seven times longer in environments with homogeneously distributed resources compared with areas of low resource homogeneity. Contrary to previous work, we found no significant effect of resource availability, diet, flight type, migratory status or body mass on the non‐migratory movements of birds. Main conclusions We suggest that longer movements in homogeneous environments might reflect the need for different habitat types associated with foraging and reproduction. This highlights the importance of landscape complementarity, where habitat patches within a landscape include a range of different, yet complementary resources. As habitat homogenization increases, it might force birds to travel increasingly longer distances to meet their diverse needs.

A habitat‐based approach to predict impacts of marine protected areas on fishers - João B. Teixeira; Rodrigo L. Moura; Morena Mills; Carissa Klein; Christopher J. Brown; Vanessa M. Adams; Hedley Grantham; Matthew Watts; Deborah Faria; Gilberto M. Amado‐Filho; Alex C. Bastos; Reinaldo Lourival; et al. (Conservation Biology, 2018)
Although marine protected areas can simultaneously contribute to biodiversity conservation and fisheries management, the global network is biased toward particular ecosystem types because they have been established primarily in an ad hoc fashion. The optimization of trade‐offs between biodiversity benefits and socioeconomic values increases success of protected areas and minimizes enforcement costs in the long run, but it is often neglected in marine spatial planning (MSP). Although the acquisition of spatially explicit socioeconomic data is perceived as a costly or secondary step in MSP, it is critical to account for lost opportunities by people whose activities will be restricted, especially fishers. We developed an easily reproduced habitat‐based approach to estimate the spatial distribution of opportunity cost to fishers in data‐poor regions. We assumed the most accessible areas have higher economic and conservation values than less accessible areas and their designation as no‐take zones represents a loss of fishing opportunities. We estimated potential distribution of fishing resources from bathymetric ranges and benthic habitat distribution and the relative importance of the different resources for each port of total catches, revenues, and stakeholder perception. In our model, we combined different cost layers to produce a comprehensive cost layer so that we could evaluate of trade‐offs. Our approach directly supports conservation planning, can be applied generally, and is expected to facilitate stakeholder input and community acceptance of conservation.

Genetic structure and diversity of a rare woodland bat, Myotis bechsteinii: comparison of continental Europe and Britain - Patrick G. R. Wright; Patrick B. Hamilton; Henry Schofield; Anita Glover; Christopher Damant; Ian Davidson-Watts; Fiona Mathews (Conservation Genetics, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

CO 2 exchange and evapotranspiration across dryland ecosystems of southwestern North America - Joel A. Biederman; Russell L. Scott; Tom W. Bell; David R. Bowling; Sabina Dore; Jaime Garatuza‐Payan; Thomas E. Kolb; Praveena Krishnan; Dan J. Krofcheck; Marcy E. Litvak; Gregory E. Maurer; Tilden P. Meyers; et al. (Global Change Biology, 2017)
Global‐scale studies suggest that dryland ecosystems dominate an increasing trend in the magnitude and interannual variability of the land CO 2 sink. However, such analyses are poorly constrained by measured CO 2 exchange in drylands. Here we address this observation gap with eddy covariance data from 25 sites in the water‐limited Southwest region of North America with observed ranges in annual precipitation of 100–1000 mm, annual temperatures of 2–25°C, and records of 3–10 years (150 site‐years in total). Annual fluxes were integrated using site‐specific ecohydrologic years to group precipitation with resulting ecosystem exchanges. We found a wide range of carbon sink/source function, with mean annual net ecosystem production ( NEP ) varying from ‐350 to +330 gC m −2 across sites with diverse vegetation types, contrasting with the more constant sink typically measured in mesic ecosystems. In this region, only forest‐dominated sites were consistent carbon sinks. Interannual variability of NEP , gross ecosystem production ( GEP ), and ecosystem respiration (R eco ) was larger than for mesic regions, and half the sites switched between functioning as C sinks/C sources in wet/dry years. The sites demonstrated coherent responses of GEP and NEP to anomalies in annual evapotranspiration ( ET ), used here as a proxy for annually available water after hydrologic losses. Notably, GEP and R eco were negatively related to temperature, both interannually within site and spatially across sites, in contrast to positive temperature effects commonly reported for mesic ecosystems. Models based on MODIS satellite observations matched the cross‐site spatial pattern in mean annual GEP but consistently underestimated mean annual ET by ~50%. Importantly, the MODIS ‐based models captured only 20–30% of interannual variation magnitude. These results suggest the contribution of this dryland region to variability of regional to global CO 2 exchange may be up to 3–5 times larger than current estimates.

Joint associations of blood plasma proteins with overwinter survival of a large mammal - Romain Garnier; Christopher K. Cheung; Kathryn A. Watt; Jill G. Pilkington; Josephine M. Pemberton; Andrea L. Graham (Ecology Letters, 2017)
In many wild animal populations, hosts are at risk of parasites and malnutrition and resource costs of defence may be difficult to afford. We postulate that proteins, important in homeostasis and immunity, play a complex but central role in condition dependence and resource costs of mammalian immune defence. To test this, we measured plasma concentrations of albumin, total proteins. Self‐reactive antibodies and parasite‐specific IgG in female Soay sheep. Using a principal component analysis, we found a new metric of condition reflecting individual variation in acquisition, assimilation and/or recycling of plasma proteins that predicted overwinter survival. Controlling for this metric, an age‐dependent trade‐off between antibody titres and protein reserves emerged, indicating costs of mounting an antibody response: younger individuals survived best when prioritising immunity while older individuals fared better when maintaining high‐protein nutritional plane. These findings suggest fascinating roles for protein acquisition and allocation in influencing survival in wild animal populations.

Quantifying the response of wheat (Triticum aestivum L) root system architecture to phosphorus in an Oxisol - Richard J. Flavel; Christopher N. Guppy; Matthew K. Tighe; Michelle Watt; Iain M. Young (Plant and Soil, 2014)

Endothelial Activation and Chemoattractant Expression are Early Processes in Isolated Blast Brain Injury - Jane E. Risdall; Alun J. Carter; Emrys Kirkman; Sarah A. Watts; Christopher Taylor; David K. Menon (NeuroMolecular Medicine, 2014)

Improving the science-policy dialogue to meet the challenges of biodiversity conservation: having conversations rather than talking at one-another - Juliette C. Young; Kerry A. Waylen; Simo Sarkki; Steve Albon; Ian Bainbridge; Estelle Balian; James Davidson; David Edwards; Roddy Fairley; Ceri Margerison; Davy McCracken; Roger Owen; et al. (Biodiversity and Conservation, 2014)

Bergmann's rule is maintained during a rapid range expansion in a damselfly - Christopher Hassall; Simon Keat; David J. Thompson; Phillip C. Watts (Global Change Biology, 2014)
Climate‐induced range shifts result in the movement of a sample of genotypes from source populations to new regions. The phenotypic consequences of those shifts depend upon the sample characteristics of the dispersive genotypes, which may act to either constrain or promote phenotypic divergence, and the degree to which plasticity influences the genotype–environment interaction. We sampled populations of the damselfly Erythromma viridulum from northern Europe to quantify the phenotypic (latitude–body size relationship based on seven morphological traits) and genetic (variation at microsatellite loci) patterns that occur during a range expansion itself. We find a weak spatial genetic structure that is indicative of high gene flow during a rapid range expansion. Despite the potentially homogenizing effect of high gene flow, however, there is extensive phenotypic variation among samples along the invasion route that manifests as a strong, positive correlation between latitude and body size consistent with Bergmann's rule. This positive correlation cannot be explained by variation in the length of larval development (voltinism). While the adaptive significance of latitudinal variation in body size remains obscure, geographical patterns in body size in odonates are apparently underpinned by phenotypic plasticity and this permits a response to one or more environmental correlates of latitude during a range expansion.

Society, demography and genetic structure in the spotted hyena - KAY E. HOLEKAMP; JENNIFER E. SMITH; CHRISTOPHER C. STRELIOFF; RUSSELL C. VAN HORN; HEATHER E. WATTS (Molecular Ecology, 2012)
Spotted hyenas ( Crocuta crocuta ) are large mammalian carnivores, but their societies, called ‘clans’, resemble those of such cercopithecine primates as baboons and macaques with respect to their size, hierarchical structure, and frequency of social interaction among both kin and unrelated group‐mates. However, in contrast to cercopithecine primates, spotted hyenas regularly hunt antelope and compete with group‐mates for access to kills, which are extremely rich food sources, but also rare and ephemeral. This unique occurrence of baboon‐like sociality among top‐level predators has favoured the evolution of many unusual traits in this species. We briefly review the relevant socio‐ecology of spotted hyenas, document great demographic variation but little variation in social structure across the species’ range, and describe the long‐term fitness consequences of rank‐related variation in resource access among clan‐mates. We then summarize patterns of genetic relatedness within and between clans, including some from a population that had recently gone through a population bottleneck, and consider the roles of sexually dimorphic dispersal and female mate choice in the generation of these patterns. Finally, we apply social network theory under varying regimes of resource availability to analyse the effects of kinship on the stability of social relationships among members of one large hyena clan in Kenya. Although social bonds among both kin and non‐kin are weakest when resource competition is most intense, hyenas sustain strong social relationships with kin year‐round, despite constraints imposed by resource limitation. Our analyses suggest that selection might act on both individuals and matrilineal kin groups within clans containing multiple matrilines.

The Multiple Faces of Valosin-Containing Protein-Associated Diseases: Inclusion Body Myopathy with Paget’s Disease of Bone, Frontotemporal Dementia, and Amyotrophic Lateral Sclerosis - Angèle Nalbandian; Sandra Donkervoort; Eric Dec; Mallikarjun Badadani; Veeral Katheria; Prachi Rana; Christopher Nguyen; Jogeshwar Mukherjee; Vincent Caiozzo; Barbara Martin; Giles D. Watts; Jouni Vesa; et al. (Journal of Molecular Neuroscience, 2011)

Field estimates of reproductive success in a model insect: behavioural surrogates are poor predictors of fitness - David J. Thompson; Christopher Hassall; Chris D. Lowe; Phillip C. Watts (Ecology Letters, 2011)
Ecology Letters (2011) 14 : 905–913 Abstract Understanding, and therefore measuring, factors that determine fitness is a central problem in evolutionary biology. We studied a natural population of Coenagrion puella (Odonata: Zygoptera) over two entire breeding seasons, with over a thousand individuals uniquely marked and genotyped, and all mating events at the rendezvous site recorded. Using a parentage analysis, fitness of individuals in the first generation was quantified as the numbers of offspring that survived to maturity. Although mating behaviour can be predicted by environmental and demographical variables, the numbers of mature offspring produced (fitness) cannot, and crucially, are poorly correlated with behavioural observations of mating. While fitness of both sexes was positively related to mating behaviour and to female’s ectoparasite burden, these behavioural observations explained little more variance in offspring production than environmental and demographical variables. Thus, we demonstrate that behavioural measures of reproductive success are not necessarily reliable estimates of fitness in natural populations.

Estimating soil strength in the rooting zone of wheat - Andrew Peter Whitmore; W. Richard Whalley; Nigel R. A. Bird; Christopher W. Watts; Andrew S. Gregory (Plant and Soil, 2011)

The emergence of biodiversity conflicts from biodiversity impacts: characteristics and management strategies - Juliette C. Young; Mariella Marzano; Rehema M. White; David I. McCracken; Steve M. Redpath; David N. Carss; Christopher P. Quine; Allan D. Watt (Biodiversity and Conservation, 2010)

Emergence of Complex Haplotypes from Microevolutionary Variation in Sequence and Structure of Colias Phosphoglucose Isomerase - Baiqing Wang; Ward B. Watt; Christopher Aakre; Noah Hawthorne (Journal of Molecular Evolution, 2009)

A Landscape Approach for Detecting and Evaluating Change in a Semi-Arid Environment - William G. Kepner; Christopher J. Watts; Curtis M. Edmonds; John K. Maingi; Stuart E. Marsh; Gonzalo Luna (Environmental Monitoring and Assessment, 2000)

Impacts of Land Degradation on Historical Temperature Records from the Sonoran Desert - Robert C. Balling; Jeffrey M. Klopatek; Mark L. Hildebrandt; Cherie K. Moritz; Christopher J. Watts (Climatic Change, 1998)

Enzyme markers in inbred rat strains: Genetics of new markers and strain profiles - Mark Adams; Peter R. Baverstock; Christopher H. S. Watts; George A. Gutman (Biochemical Genetics, 1984)